European Model of Protection of the Consumers’ Rights in Distance Contracts – on the Example of Withdrawal Right - Lakerbaia, Tamar (Journal of Law, 2017)
Article provides discussion of the characteristics of contracts made with participation of consumers via distance communication. It describes European standards of the consumers rights ’ protection in distance contracts that is the right of withdrawal. Article analyses the characteristics of formation of consumers will in the contractual relations and protective effect of the right of withdrawal.